Food toxicology: quantitative analysis of the research field literature. (2nd January 2020) - Yeung, Andy Wai Kan; Tzvetkov, Nikolay T.; Jóźwik, Artur; Horbanczuk, Olaf K.; Polgar, Timea; Pieczynska, Magdalena D.; Sampino, Silvestre; Nicoletti, Ferdinando; Berindan-Neagoe, Ioana; Battino, Maurizio; Atanasov, Atanas G.
Abstract: Total-scale quantitative research literature analysis on the food toxicology scientific field has yet to be conducted. In this work, we identified and analysed food toxicology publications in the existing scientific literature. A literature search was performed with the online Web of Science database. Full records and cited references of the 73, 099 identified manuscripts were imported into VOSviewer software for analysis. This research field has been growing steadily since the 1990s. Article to review ratio was 7.4:1. The publications were mainly related to toxicology, environmental sciences, food science and technology, pharmacology/pharmacy and biochemistry/molecular biology. The United States and China are major contributors to food toxicology research, followed by other European and Asian countries. The prolific authors have formed three major clusters within a citation network. Toxic or hazardous chemicals related to food with high citations included aflatoxin, dioxin, fumonisin, malondialdehyde, mycotoxin, ochratoxin, phthalate, and polychlorinated biphenyl.